Screening of organic and metal contaminants in Australian humpback dolphins (Sousa sahulensis) inhabiting an urbanised embayment. (May 2016) - Weijs, Liesbeth; Vijayasarathy, Soumini; Villa, C. Alexander; Neugebauer, Frank; Meager, Justin J.; Gaus, Caroline
Abstract: As a marine mammal species that inhabits shallow nearshore waters, humpback dolphins are likely exposed to a wide range of pollutants from adjacent land-based activities. Increased mortality rates of Australian humpback dolphins ( Sousa sahulensis ) in waters off a major urbanised centre triggered investigations into the threats to these species, including their contaminant exposure. The present study utilised archived tissues from 6 stranded animals to screen for a range of pollutants (PCDD/Fs, PBDEs, PCBs, organochlorine pesticides, PAHs, organotins, essential and non-essential elements) to inform future biopsy based biomonitoring strategies. Concentrations of PCBs and DDXs in blubber of some of these animals were remarkably high, at levels near or above toxicological thresholds associated with immune- and reproductive toxicity or population declines in other marine mammals. PBDEs, PAHs, HCB, organotins, 'drins' as well as other organic pesticides were not detected, or present at relatively low concentrations. Profiles of elements were similar in epidermis compared to other tissues, and apart from some exceptions (e.g. Fe, Cr, Co, Cu) their concentrations fell within 25th–75th percentiles of cetacean baselines in four of the five animals. Non-essential elements (Al, V, Pb, Ba, Ni, Cd) were notably elevated in one specimen which may have experienced poor health or nutritional status. These data provide a first insight into the contaminant status of a rare and poorly studied population inhabiting an urbanised area. The results highlight a need for future biomonitoring of live populations, and inform on priorities in the typically limited blubber and skin sample volumes obtained through biopsies. Highlights: Australian humpback dolphins are exposed to a variety of pollutants. Levels of PCBs and DDXs in blubber were near or above toxicity thresholds. PBDEs, PAHs, HCB, organotins, other POPs and 'drins' were not detected or at low levels. Element profiles were similar in epidermis compared to other tissues. Results useful for prioritizing pollutants for biopsy samples from this population.